2022
DOI: 10.6004/jadpro.2022.13.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Pull Up a Seat: Engaging Patients as Empowered Partners in Health Equity Transformation

Abstract: At the JADPRO Live Virtual 2021 keynote interview, Maimah Karmo, CEO and Founder of the Tigerlily Foundation, spoke with Amy Pierre, MSN, ANP-BC, on her breast cancer experience and drive to establish an organization that educates, advocates for, and empowers young women of color at every stage of their breast cancer journey. Ms. Karmo and Ms. Pierre also discussed the role of the advanced practitioner in furthering patient-centered, equitable care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This approach offers a genuine and meaningful community engagement experience rather than just a performative step taken by sponsors during trial recruitment. 109 A recent study examined community-based interventions related to triple-negative BC over the past 10 years. It revealed that most prospective studies primarily focused on screening, diagnosis, and treatment, with a minimum focus on addressing social determinants and incorporating participatory research principles.…”
Section: Facilitators Of Diversity Equity and Inclusionmentioning
confidence: 99%
“…This approach offers a genuine and meaningful community engagement experience rather than just a performative step taken by sponsors during trial recruitment. 109 A recent study examined community-based interventions related to triple-negative BC over the past 10 years. It revealed that most prospective studies primarily focused on screening, diagnosis, and treatment, with a minimum focus on addressing social determinants and incorporating participatory research principles.…”
Section: Facilitators Of Diversity Equity and Inclusionmentioning
confidence: 99%